Manual of objectives tests to acompany. Basic marketing a managerial approach / E. Jerome McCarthy, William D. Perreault - McCarthy, E. Jerome [et.al] (1984)
Marketing´s role in society, marketing´s role within the firm, finding attractive marketing oppotunities, uncontrollable environments affecting marketing management, getting information for marketing, industrial and intermediate customers and their Buying Behavior, place and develpment of channel systems, demographic dimensions of the consumer.